2015
DOI: 10.1089/pop.2014.0043
|View full text |Cite
|
Sign up to set email alerts
|

Improving Population Management through Pharmacist-Primary Care Integration: A Pilot Study

Abstract: Pharmacists have unique skills that may benefit primary care practices. The objective of this demonstration project was to determine the impact of integrating pharmacists into patient-centered medical homes, with a focus on population management. Pharmacists were partnered into 5 primary care practices in Vermont 1 day per week to provide direct patient care, population-based medication management, and prescriber education. The main measures included a description of drug therapy problems identified and cost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…‘Drug use without indication’ or ‘unnecessary therapy’ is common in studies conducted in hospitals . ‘Non‐adherence’ and ‘adverse drug reaction’ are more common to studies conducted in primary care and are more often detected by patient interviews . ‘Drug indicated but not prescribed’ is also frequent in some studies .…”
Section: Discussionmentioning
confidence: 99%
“…‘Drug use without indication’ or ‘unnecessary therapy’ is common in studies conducted in hospitals . ‘Non‐adherence’ and ‘adverse drug reaction’ are more common to studies conducted in primary care and are more often detected by patient interviews . ‘Drug indicated but not prescribed’ is also frequent in some studies .…”
Section: Discussionmentioning
confidence: 99%
“…56 In the HealthOne Mount Druitt project (Australia), consultations also included 'more informal exchanges of information.' 80 Different patients might also have different but often overlapping provider networks, and these overlaps offered the greatest scope for strengthening care co-ordination. 67 Most papers described what care co-ordination activities MCP-like interorganisational networks undertook rather than how these co-ordination arrangements were created or (in the realist sense) their contexts.…”
Section: Interorganisational Network Managementmentioning
confidence: 99%
“…91 In the Australian HealthOne Mount Druitt project, boundary-spanner care co-ordinators made patients feel more supported and less anxious and thus reduced hospital visits. 90 A reanalysis of administrative data in PCMHs and ACOs that involved pharmacists 80 found that pharmacists identified 708 drug therapy problems through direct patient care (336/708; 47.5%), population-based strategies (276/708; 38.9%) and education (96/708; 13.6%). Pharmacists combining academic detailing with direct patient care and population-based medication management probably helped to optimise patient outcomes.…”
Section: Causal Link 3:11 -Multidisciplinary Team Working Diverts Patmentioning
confidence: 99%
See 2 more Smart Citations